Determining Model of Halal Lifestyle: A Study on the Role of Kopontren - Annisa, Arna Asna (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
The gap between the growth of the global halal industry and the people's halal lifestyle must be fixed immediately. This study aims to analyze the halal lifestyle in pondok pesantrens known to have a character education pattern in their curriculum. This phenomenological research was carried out by in-depth interviews with caregivers and students at the Pondok Pesantren Edi Mancoro and observations. The results of data processing with Atlas t.i show that the leading sector in the development of halal values in Pondok pesantren is Kopontren. With a participatory education pattern, Kopontren involves students in procuring goods and evaluating daily halal needs. The exemplary caregivers also determine the pattern of halal consumption so that the halal lifestyle becomes the morals of the students and becomes an example for society. This novelty research is the first community-based halal value development model and can be used as a recommendation for the development of the Indonesian halal industry.